Positive Solution to a Fractional Boundary Value Problem - A. Guezane-Lakoud; R. Khaldi (International Journal of Differential Equations)
A fractional boundary value problem is considered. By means of Banach contraction principle, Leray-Schauder nonlinear alternative, properties of the Green function, and Guo-Krasnosel'skii fixed point theorem on cone, some results on the existence, uniqueness, and positivity of solutions are obtained.